2022
DOI: 10.3389/fimmu.2022.1037214
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-based clinical protection against SARS-CoV-2 infection and the humoral immune response: A 1-year follow-up study of patients with multiple sclerosis receiving ocrelizumab

Abstract: IntroductionGiven the varying severity of coronavirus disease 2019 (COVID-19) and the rapid spread of Severe-Acute-Respiratory-Syndrome-Corona-Virus-2 (SARS-CoV-2), vaccine-mediated protection of particularly vulnerable individuals has gained increasing attention during the course of the pandemic.MethodsWe performed a 1-year follow-up study of 51 ocrelizumab-treated patients with multiple sclerosis (OCR-pwMS) who received COVID-19 vaccination in 2021. We retrospectively identified 37 additional OCR-pwMS, 42 pw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…In our study, repetitive vaccination or infection with SARS-CoV-2 upon anti-CD20 treatment resulted in only a slight increase in the anti-spike protein response. This is controversially discussed among a few reports, with some reporting improved and some describing sustained low antibody levels in pwMS under anti-CD20 therapy [ 34 , 35 , 41 , 42 , 43 , 44 ]. The minor increase in the number of pwMS who seroconvert under anti-CD20, and the greater proportion of those who do the same under ns-S1P, mirrors the vaccination response.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, repetitive vaccination or infection with SARS-CoV-2 upon anti-CD20 treatment resulted in only a slight increase in the anti-spike protein response. This is controversially discussed among a few reports, with some reporting improved and some describing sustained low antibody levels in pwMS under anti-CD20 therapy [ 34 , 35 , 41 , 42 , 43 , 44 ]. The minor increase in the number of pwMS who seroconvert under anti-CD20, and the greater proportion of those who do the same under ns-S1P, mirrors the vaccination response.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, only 25% of patients treated with ocrelizumab (25%) generated detectable protective IgG levels 8 weeks following COVID-19 mRNA vaccination, and this response was not maintained 24 or 36 weeks post vaccination [ 64 ]. However, in another study, a sequential increase in the proportion of patients with antibody response after each booster dose was found, and, after booster vaccinations with four doses, 90% of patients treated with ocrelizumab developed an antibody response [ 65 ]. In a study comparing antibody response on rituximab and ocrelizumab, both groups demonstrated reduced antibody levels compared to untreated patients (ocrelizumab 201-fold decrease and rituximab 20-fold decrease) [ 66 ].…”
Section: Vaccine Responsementioning
confidence: 99%
“…10 However, these studies did not measure serology in all participants, instead focussing on clinical infection. Lack of seroconversion after initial vaccination, especially in the context of anti-CD20 and S1P treatments, has been reported to be associated with increased rates of COVID-19 by some, [11][12][13][14] but not all, 15 groups. The differential protective effect of vaccination against severe infections in those exposed to DMT associated with lower seroconversion is less clear, given the relative rarity of severe infection in the post-vaccination era.…”
Section: Risk Of Covid-19 In People With Multiple Sclerosis Who Are S...mentioning
confidence: 99%